2001
DOI: 10.1300/j144v03n01_19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Microbial Inoculant on Stomatal Response of Maize Leaves

Abstract: more slowly (i.e., remained open longer) for the EM-treated plants compared with the water-treated control plants. There was no effect of EM on cuticular conductance in any of the experiments. The results of this study indicate that EM cultures contains bioactive substances that can significantly affect leaf stomatal response. [Article copies available for a fee from The Haworth Document Delivery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Although above‐ground fresh and dry weights were higher under Osmocote fertilisation compared with vermicompost fertilisation, the effect of vermicompost tea was most pronounced under vermicompost fertilisation. Soluble mineral nutrients and microbial by‐products in vermicompost tea can enhance nutrient uptake from the soil and increase foliar uptake of nutrients 4, 32. Nutrient analysis indicated that vermicompost tea supplied a considerable amount of soluble mineral nutrients to plants compared with the control (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 98%
“…Although above‐ground fresh and dry weights were higher under Osmocote fertilisation compared with vermicompost fertilisation, the effect of vermicompost tea was most pronounced under vermicompost fertilisation. Soluble mineral nutrients and microbial by‐products in vermicompost tea can enhance nutrient uptake from the soil and increase foliar uptake of nutrients 4, 32. Nutrient analysis indicated that vermicompost tea supplied a considerable amount of soluble mineral nutrients to plants compared with the control (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 98%
“…4), probably due to maintenance of the physiological balance (Martin and Botton, 1993;Smith and Read, 2008). Xu et al (2008) found that maize stomata of nonwatered plants treated by EM respond more quickly and efficiently in comparison to plants well-watered and without EM. This can be an indirect beneficial of microorganisms on production of some phytohormones, and enhance of growth, development and further plant response efficiency to stress factors.…”
Section: Resultsmentioning
confidence: 95%
“…Available soluble mineral nutrients and microbial secondary products in vermicompost tea may balance nutrients simplified for plants, improve nutrient uptake from the soil, and promote foliar uptake of nutrients. (Xu et al, 2001, Ingham, 2005and Najafabadi, 2014. According to the results of previous studies, vermicompost tea favorably improved plant growth and the concentration of minerals in plants (Sanwal et al, 2006;Hargreaves et al, 2008).…”
Section: Discussionmentioning
confidence: 99%